Influence of Herbal Active D on Nursery Pig Growth Performance - Larissa L. Becker; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Joel M. DeRouchey; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 2,268 pigs (L337 × 1050 PIC; initially 12.1 ± 0.39 lb) were used in a 42-d growth study to evaluate the effects of herbal active D on growth performance, bone characteristics, and serum parameters of nursery pigs. Pigs were weaned at approximately 21 d of age and randomly allotted to 1 of 3 dietary treatments in a randomized complete block design. A total of 84 pens were used with 27 pigs per pen and 28 replications per treatment across 2 rooms. Pens were blocked by BW and weaning date. Dietary treatments were corn-soybean meal-based and fed in 3 phases. Treatment diets consisted of a control (contained 1,650 IU/kg of vitamin D3), or control with the addition of 120 or 200 mg/kg of herbal active D (Phytobiotics, St. Louis, MO). At the end of the study, 10 pigs per treatment were euthanized and the right fibula, metacarpal, 2nd rib, and 10th rib were collected to determine bone density, bone breaking strength, and percentage bone ash by utilizing the de-fatted processing method. Overall (d 0 to 42), there was a marginally significant (P= 0.067) worsening of feed efficiency as inclusion of herbal active D increased but no effect (P>0.10) on final BW, overall ADG, ADFI, or mortality. There was a bone × treatment interaction for bone density, where increasing herbal active D increased bone density for the 2nd rib(P= 0.012), but there was no difference between treatments for other bones (P>0.10). For bone breaking strength and bone ash, there was no evidence (P>0.10) of an interaction. For bone breaking strength, the metacarpal had greater breaking strength (P<0.001) compared to all other bones, followed by the fibula and 10th rib, with the 2nd rib having the lowest bone breaking strength. For percentage bone ash, there was significant linear increase (P= 0.026) across all bones as herbal active D increased. For bone ash weight, the metacarpals and 10th ribs had the highest bone ash weight followed by the fibula, with 2nd rib having the lowest (P<0.05) bone ash weight. Additionally, there was no difference (P>0.10) across treatments for porcine circovirus type 2 S/P ratio, porcine reproductive and respiratory syndrome,Mycoplasma hyopneumoniae, 25(OH)D3status or circulating cytokine concentrations except for IL-8 concentrations which increased linearly (P= 0.027) as herbal active D increased. However, a day effect was observed (P<0.001) with higher values for antibodies and cytokine concentrations on d 21 compared to d 42, except for IL-1ra and IL-8 having no significant (P>0.10) day effect. In summary, herbal active D inclusion had minimal impact on growth or serum parameters; however, herbal active D increased percentage bone ash.
Keywords: nursery pig; vitamin D; growth performance; bone characteristics